Mental Disorders Theoretical and Empirical Perspectives - Woolfolk, Robert; Allen, Lesley (IntechOpen, 2013)
This book brings together an international array of stars of the mental health professions to create a cutting edge volume that sheds light on many important and heretofore poorly understood issues in psychopathology. Mental Disorders-Theoretical and Empirical perspectives will be an important addition to the libraries of scholars and clinicians.